Influence of Stoichiometry on the Thrust and Heat Deposition of On‐Chip Nanothermites. Issue 3 (29th January 2018) - Ramachandran, Raghav; Vuppuluri, Vasant S.; Fleck, Trevor J.; Rhoads, Jeffrey F.; Gunduz, Ibrahim E.; Son, Steven F.
Abstract: Currently, there is very little systematic work quantifying the thrust or heat applied to an electronic circuit or other substrate by a deposited layer of energetic material. A better understanding of the interactions between nanoscale energetic materials and electronic systems, as a function of stoichiometry, is needed. For this purpose, formulations of nAl‐CuO and nAl‐Bi2 O3 nanothermites were prepared at different equivalence ratios and selectively deposited onto electronic circuit analogues (silicon wafers) and the amounts of thrust production and heat deposition were measured. Both nanothermite systems produced maximum thrust near stoichiometric ratios, accompanied by a shock wave, with minimal thermal effects due to large gas production, which ejects the hot products of the substrates. Conversely, more fuel‐rich mixtures led to significantly decreased thrust while increasing heat deposition due to the lower gas production, which allowed more heat to diffuse to the substrates. This shows that the energetic material response can be tuned between thrust or heat deposition by just varying the equivalence ratio. The conductive heat transfer within the silicon substrates from the nAl‐CuO system increased more than the nAl‐Bi2 O3 system at fuel rich conditions due to its higher heat of combustion. Abstract :